2018
DOI: 10.1002/ppap.201800095
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ammonia‐derived species on visible‐light photocatalytic activity of Au supported on amorphous TiO2 activated by plasma

Abstract: Amorphous TiO 2 supported Au photocatalyst (Au/AmT) is prepared via modified impregnation method with ammonia washing, followed by cold plasma treatment to activate the photocatalysts. Residual ammonia ([NH 3 ] s ) is formed due to the hydrogen bond between surface OH groups on AmT and ammonia. The [NH 3 ] s suppressed the reduction of Au δ+ and occupied active sites, leading to a poor activity of as-prepared Au/AmT. The performance of cold plasmas in activation strongly depends on discharge gases. N 2 and O 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 41 publications
(50 reference statements)
0
7
0
Order By: Relevance
“…Interestingly, the researchers found that the performance of the synthesized gold catalytic materials strongly depends on discharge gases and discharge parameters. Sun et al [141] used AP DBD cold plasma with various working gases to activate the amorphous TiO 2 supported Au photocatalytic material (Au/AmT) obtained via a modified impregnation method with ammonia washing. Residual ammonia ([NH 3 ] s ) was formed due to the hydrogen bond between surface OH groups on AmT and ammonia.…”
Section: Cold Plasma Reduction Of Catalytic Materialsmentioning
confidence: 99%
“…Interestingly, the researchers found that the performance of the synthesized gold catalytic materials strongly depends on discharge gases and discharge parameters. Sun et al [141] used AP DBD cold plasma with various working gases to activate the amorphous TiO 2 supported Au photocatalytic material (Au/AmT) obtained via a modified impregnation method with ammonia washing. Residual ammonia ([NH 3 ] s ) was formed due to the hydrogen bond between surface OH groups on AmT and ammonia.…”
Section: Cold Plasma Reduction Of Catalytic Materialsmentioning
confidence: 99%
“…A schematic of the photocatalytic hydrogen production reaction using P-In 2 S 3 is shown in Figure 6 c. After the plasma treatment of bare In 2 S 3 , the atomic arrangement of the nanosheets is altered to form an amorphous surface layer based on the bombardment from the plasma gas [ 40 , 41 , 42 ]. The amorphous region in the In 2 S 3 nanosheets creates an unsaturated coordination environment to tune the electron structure.…”
Section: Resultsmentioning
confidence: 99%
“…The conventional TiO 2 (P25, Degussa) and B-TiO 2 (Shanghai Institute of Ceramics, China) were used as photocatalysts to construct the PPS, respectively. To prepare the photocatalyst's coating (as mentioned in the introduction), about 35 mg sample was coated on a glass substrate of 75 mm (length)×25 mm (width)×1 mm (thickness) using a drip-coating method and dried at 80 °C for 1 h [11,14]. The weight of the coated sample was controlled within 35±1 mg.…”
Section: Preparation Of Photocatalystsmentioning
confidence: 99%
“…The intermediate products during the toluene removal process were also evaluated by a mass spectrometer (HPR 20 QIC, HIDEN Analytical, United Kingdom). For comparison, photocatalytic performance of the photocatalysts in toluene removal was investigated in a single-pass continuous-flow photocatalytic oxidation reactor [11,15]. A xenon lamp (within 300-800 nm range) located at the top of the quartz window of the photocatalytic oxidation reactor was used as the light source [16], and the light intensity on the surface of the photocatalysts was measured by an optical power and energy meter (PM100USB, Thorlabs, USA) [11].…”
Section: Plasma Photocatalytic Removal Of Toluenementioning
confidence: 99%
See 1 more Smart Citation